Synchronization of ovulation and subsequent fertility in buffaloes followingPGF2Î±-PGF2Î± protocol, with or without GnRH - DADARWAL, D; GHUMAN, S P S; HONPARKHE, M; SINGH4, JAGIR (The Indian Journal of Animal Sciences, 2011)
A PGF2α-based protocol, with or without GnRH, was used to synchronize ovulation and assess subsequent fertility in cycling buffaloes. In protocol-A (n=6) and protocol-B (n=6), buffaloes were administered, at unknown stage of estrous cycle, 2 PGF2α injections (1 mg cloprostenol each) 12 days apart, whilst buffaloes of protocol-B received an additional GnRH injection (0.02 mg buserelin) at 48 h after second-PGF2α. Buffaloes were artificially inseminated (AI) twice at 48 and 72 h after second-PGF2α. The luteal profile of day 0 reached basal values in all the buffaloes at 72 h subsequent to first-PGF2α on day 0. The ovulatory follicles observed on day 0, ovulated between 48–120 h subsequent to first-PGF2α in 92 per cent buffaloes. In response to second-PGF2α on day 12, all the buffaloes exhibited luteal regression and displayed onset of estrus around 24 h after second-PGF2α. Ovulation in response to second-PGF2α induced luteolysis was observed in all the buffaloes between 72–96 h after second-PGF2α. Conception of buffaloes was similar across treatments at 42nd day (50%). The administration of GnRH in protocol-B had no effect on time of ovulation or conception. In summary, 2 injections of PGF2α administered 12 day apart in cycling buffaloes were highly efficacious for synchronizing ovulation and thus, permitting fixed-time AI at 72 h after second-PGF2α which results in good enough fertility